2020
DOI: 10.4067/s0718-48082020000100005
|View full text |Cite
|
Sign up to set email alerts
|

Mejora de la motivación en estudiantes inmigrantes latinoamericanos mediante un programa de mindfulness: un estudio aleatorizado

Abstract: Este trabajo se ha llevado a cabo en el marco del Proyecto Nacional I+D del Ministerio de Economía y Competitividad de España [Ref: EDU2011-26887]: "Educación para la salud transcultural en los jóvenes, inmigrantes y autóctonos, de Almería: Análisis e intervención para su optimización y mejora".Mejora motivación en estudiantes mediante un programa de mindfulness 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…The results showed that after the intervention, students improved several cognitive skills and gained self-awareness and self-esteem. Franco et al (2020) worked on an experimental study in which they applied a psychoeducational mindfulness program to evaluate the achievement and learning motivations of Latin American students living in Spain. The study highlighted the benefits of implementing a mindfulness training program within the academic curriculum.…”
Section: Impact Of Mindfulness On Learning Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that after the intervention, students improved several cognitive skills and gained self-awareness and self-esteem. Franco et al (2020) worked on an experimental study in which they applied a psychoeducational mindfulness program to evaluate the achievement and learning motivations of Latin American students living in Spain. The study highlighted the benefits of implementing a mindfulness training program within the academic curriculum.…”
Section: Impact Of Mindfulness On Learning Abilitiesmentioning
confidence: 99%
“…Franco et al . (2020) worked on an experimental study in which they applied a psychoeducational mindfulness program to evaluate the achievement and learning motivations of Latin American students living in Spain.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Viciana et al (2018), y Bonilla y Padilla (2015) resaltan que los programas de intervención terapéutica que incluyen la aplicación de técnicas del mindfulness para la obtención de beneficios en la reducción de estrés resultan cada vez más promisorios. Asimismo, Hervás et al (2016), Cuevas et al (2017), Alvarado y Burmester (2018), Oblitas et al (2019), Franco et al (2020), informan que la aplicación de estas prácticas en el entorno académico es cada vez más frecuentada, debido a los beneficios que pueden obtenerse para reducir el estrés en los estudiantes, lo que produce una optimización del proceso de aprendizaje.…”
Section: Introductionunclassified